Polio eradication: mobilizing and managing the human resources - Aylward R. Bruce; Linkins Jennifer (The World Health Organization, 2005)
Between 1988 and 2004, the Global Polio Eradication Initiative grew to become the largest international health effort in history, operating in every country of the world. An estimated 10 million health workers and volunteers have been engaged in implementing the necessary polio supplementary immunization activities (SIAs) on a recurring basis, and at least 35 000 well-trained workers have been conducting polio surveillance. A combination of task simplification, technological innovations and adaptation of strategies to fit local circumstances has allowed the Initiative to use a wide range of workers and volunteers, from both inside and outside the health sector, to deliver the polio vaccine during SIAs and to monitor progress in virtually every area of every country, regardless of the health infrastructure, conflict, geography and/or culture. This approach has required sustained political advocacy and mass community mobilization, together with strong management and supervisory processes. Non-monetary incentives, reimbursement of costs and substantial technical assistance have been essential. Given the unique features of eradication programmes in general, and polio eradication in particular, the implications of this approach for the broader health system must continue to be studied if it is to be replicated for the delivery and monitoring of other interventions.